Comparison between azacitidine and decitabine as front-line therapy in elderly acute myeloid leukemia patients not eligible for intensive chemotherapy. (April 2023) - Maurillo, L.; Spagnoli, A.; Candoni, A.; Papayannidis, C.; Borlenghi, E.; Lazzarotto, D.; Fianchi, L.; Sciumè, M.; Zannier, M.E.; Buccisano, F.; Del Principe, M.I.; Mancini, V.; et al.
Abstract: We compared the efficacy of azacitidine (AZA) and decitabine (DEC) in elderly patients with untreated AML, diagnosed according to WHO criteria. In the two groups, we evaluated complete remission (CR), overall survival (OS) and disease free survival (DFS). The AZA and DEC groups included 139 and 186 patients, respectively. To minimize the effects of treatment selection bias, adjustments were made using the propensity-score matching method, which yielded 136 patient pairs. In the AZA and DEC cohort, median age was 75 years in both, (IQR, 71–78 and 71–77), median WBCc at treatment onset 2.5 × 10 9 /L (IQR, 1.6–5.8) and 2.9 × 10 9 /L (IQR, 1.5–8.1), median bone marrow (BM) blast count 30% (IQR, 24–41%) and 49% (IQR, 30–67%), 59 (43%) and 63 (46%) patients had a secondary AML, respectively. Karyotype was evaluable in 115 and 120 patients: 80 (59%) and 87 (64%) had intermediate-risk, 35 (26%) and 33 (24%) an adverse risk karyotype, respectively. Median number of cycles delivered was 6 (IQR, 3.0–11.0) and 4 (IQR, 2.0–9.0), CR rate was 24% vs 29%, median OS and 2-year OS rates 11.3 (95% CI 9.5–13.8) vs 12.0 (95% CI 7.1–16.5) months and 20% vs 24%, respectively. No differences in CR and OS were found within the following subgroup: intermediate- and adverse-risk cytogenetic, frequency of WBCc at treatment ≥ 5 × 10^9 L and < 5 × 10^9/L, de novo and secondary AML, BM blast count < and ≥ 30%. Median DFS for AZA and DEC treated patients was 9.2 vs 12 months, respectively. Our analysis indicates similar outcomes with AZA compared to DEC. Highlights: Azacitidine and decitabine have comparable efficacy and toxicity in elderly patients with newly diagnosed acute myeloid leukemia. Azacitidine and decitabine can be used interchangeably in combination with venetoclax or other targeted therapies. Since the toxicity of the new combination therapies is not negligible, hypomethylating drug monotherapy may still be beneficial in some subgroups of frail or very frail patients. New fitness criteria will be required to identify the most appropriate therapy in different subsets of elderly patients.